2013
DOI: 10.1080/00071668.2013.791382
|View full text |Cite
|
Sign up to set email alerts
|

Apilarnil reduces fear and advances sexual development in male broilers but has no effect on growth

Abstract: 1. An experiment was conducted to determine the possibility of stimulating sexual development at an early age in male and female broiler chickens by administration of apilarnil, a natural bee product, in the pre-pubertal period. 2. From 28 to 55 d of age, birds were given apilarnil orally. The effects of low (2.5 g/bird) and high (7.5 g/bird) doses of apilarnil on growth performance, testicular weight, secondary sexual characteristics, blood lipids, testosterone and fearful behaviour were evaluated. 3. Apilarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…This situation results in the stimulating of the spermatogenesis in men. Also, this positive result of apilarnil could be examined rather than drugs and chemicals to stimulate sexual development (Altan et al, 2013;Yücel et al, 2011). Not only the data, which has been reported on the subject of the increment of the hormone levels as an impact of the drone larvae in Eastern Europe and Asian folk medicine, demonstrates the androgen-like activity of apilarnil, but also previously described data is contributing to this characteristic feature of apilarnil in particular (Artık and Konar, 2015;Seres et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This situation results in the stimulating of the spermatogenesis in men. Also, this positive result of apilarnil could be examined rather than drugs and chemicals to stimulate sexual development (Altan et al, 2013;Yücel et al, 2011). Not only the data, which has been reported on the subject of the increment of the hormone levels as an impact of the drone larvae in Eastern Europe and Asian folk medicine, demonstrates the androgen-like activity of apilarnil, but also previously described data is contributing to this characteristic feature of apilarnil in particular (Artık and Konar, 2015;Seres et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, she measures the testosterone and cholesterol levels in blood. Administration of high dosage Apilarnil (7.5 g/day) increases the comb and testes sizes and testosterone level very significantly, also statistically significant decreasing observes in the fearful behavior and total cholesterol level [12]. These pioneer researches indicate the androgenic effect of Apilarnil.…”
Section: Introductionmentioning
confidence: 78%
“…At the end of the experiment, it was determined that the experiment group have bigger combs then controls [11]. Altan is a participant of the same research group deepened the research in 2013 [12]. She examines both comb and testes size and fearful behavior in broilers with oral administration of different dosage of Apilarnil.…”
Section: Introductionmentioning
confidence: 99%
“…Although BDL has been used in Eastern European and Asian folk medicine for increasing testosterone hormone levels for thousands of years, the androgenic activity of BDL being reported in recent studies [19,31] . Scientific studies have reported that BDL, a natural source of androgenic hormones, stimulates spermatogenesis in men and increases sexual performance [13,32,33] . In another study, it has been determined that hormone therapy in male chickens increases testicular weights and testosterone production and supports normal growth and development.…”
Section: Introductionmentioning
confidence: 99%